2015
DOI: 10.1007/978-3-319-16763-3_15
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a Larger EM-Induced Fault Model

Abstract: Electromagnetic waves have been recently pointed out as a medium for fault injection within circuits featuring cryptographic modules. Indeed, it has been experimentally demonstrated by A. Dehbaoui et al. [3] that an electromagnetic pulse, produced with a high voltage pulse generator and a probe similar to that used to perform EM analyses, was susceptible to create faults exploitable from a cryptanalysis viewpoint. An analysis of the induced faults [4] revealed that they originated from timing constraint viol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 11 publications
1
31
0
Order By: Relevance
“…Faults in an Integrated circuit (IC) are created by EMFI either directly when the logic state of some storage elements such as flip-flops is inverted, or when the propagation delay of some combinational paths is so increased that their output is stored while the right value is not arrived [3]. These previous works have focused on the impact of EMFI on a large chain of flip-flops.…”
Section: Characterization At Logical Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Faults in an Integrated circuit (IC) are created by EMFI either directly when the logic state of some storage elements such as flip-flops is inverted, or when the propagation delay of some combinational paths is so increased that their output is stored while the right value is not arrived [3]. These previous works have focused on the impact of EMFI on a large chain of flip-flops.…”
Section: Characterization At Logical Levelmentioning
confidence: 99%
“…Oumarouayache et al have presented in [2] a guidance for magnetic probe design using simulation. Further experiments by Ordas et al [3] show that different properties of the probes (e.g. number of loop) can lead to a better pulse excitation and resulting impact when testing on real target.…”
Section: Introductionmentioning
confidence: 99%
“…This is a intuitive explanation of how EMPI induces faults. However, in 2014, [10] has experimentally demonstrated that it is possible to generate faults within a circuit at rest (clocked stopped), using an enhanced EMPI platform. This means that EMPI is able to induce bitsets and bitresets.…”
Section: A State Of the Art On Em Injectionmentioning
confidence: 99%
“…3. One may observe that a HD features mainly DFFs which are, according to the EMP susceptibility model introduced in [10], the most susceptible gates, especially when their clock input toggles. DF F 1 's output (Q 1 ), which is initialized respectively at 1, switches at each rising edge of the clock.…”
Section: B Embedded Sensors To Detect Fault Attacksmentioning
confidence: 99%
See 1 more Smart Citation